2015
DOI: 10.3917/popu.1502.0265
|View full text |Cite
|
Sign up to set email alerts
|

Sida et vie religieuse au Malawi : repenser l’influence de la dynamique démographique sur les comportements culturels

Abstract: Cet article examine les relations réciproques qu’entretiennent la religion et les dynamiques démographiques au Malawi dans un contexte d’épidémie de sida, entre 2001 et 2006. À partir de données inédites sur des chefs religieux et des femmes laïques du Malawi rural, l’analyse montre que les prescriptions religieuses ont été influencées par l’épidémie. Cela se traduit par la prise en compte explicite d’informations relatives au sida dans les prescriptions religieuses en matière de sexualité et de constitution d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Research on congregational responses to the HIV epidemic in Malawi provides a clear picture of this role. Researchers found that congregations taught on the subject frequently, coordinated home visitation, youth programming, voluntary testing, and care for those affected by illness and death (Trinitapoli, 2006(Trinitapoli, , 2015. Social network research also demonstrated that informal conversations about HIV were common and served to translate formal religious teaching into practical application (Agadjanian and Menjívar, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research on congregational responses to the HIV epidemic in Malawi provides a clear picture of this role. Researchers found that congregations taught on the subject frequently, coordinated home visitation, youth programming, voluntary testing, and care for those affected by illness and death (Trinitapoli, 2006(Trinitapoli, , 2015. Social network research also demonstrated that informal conversations about HIV were common and served to translate formal religious teaching into practical application (Agadjanian and Menjívar, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in Malawi's context. Consequently, Malawian pastors and imams have demonstrated a willingness to publicly reinterpret scriptural and doctrinal teachings regarding marriage and divorce in order to address this health concern in their communities (Trinitapoli, 2015). Additionally, local chiefs and ankhoswe, or traditional marriage mediators, may assess the sexual history and health of couples in their preparation for marriage; this assessment and their instructions on responsible sexual behavior may promote community cohesion through participation in traditions while reducing the risk of spreading HIV/AIDS in their community (Trinitapoli, 2015).…”
Section: Community Cohesion and Community Carementioning
confidence: 99%